Makna Denotatif dan Konotatif Kata Benda, Kata Kerja, Kata Sifat dalam Koran Kompas Edisi Juli - Agustus 2016 Sebagai Implementasi Bahan Ajar Tingkat SMP - , Supriyanti; , Prof. Dr. Abdul Ngalim, M.M, M.Hum (2017)
This study has two objectives: (1) To describe the shape of denotative in nouns, verbs and adjectives in compass newspaper edition July-August, 2016 as a junior-level teaching materials? (2) To describe the shape of the connotative meanings of nouns, verbs and adjectives in compass newspaper edition July-August, 2016 as a junior-level teaching materials ?. In this study, researchers used a qualitative descriptive type of research is a research procedure that uses descriptive data in the form of words written or spoken of people and actors that can be observed, qualitative research to collect data instead of using numbers as a primary method. However, the form of text, words, symbols and images. The results of this study classifies data in two categories, namely, denotative and connotative. Components in denotative ie find a noun, a verb, and also said sifa. Begipun with connotative meaning component compass newspaper from July to August 2016. Based on a study of news discourse in compass letter July-August edition of 2016 data found that including the component nouns. Meaning contained in the newspaper discourse compass can be understood by the reader. Keywords: meaning, denotative, connotative meaning